Some Observations on the Coagulation Defect During Treatment with the Anticoagulant “Sintrom” - Vermeulen, H. J; ten Bokkel Huinink, S. A; Radhakishun, K. S (Thrombosis and Haemostasis, 1959)
1. The decrease of activity of prothrombin, occuring during administration of “Sintrom”, becomes only manifest when the activity of “factor VII” has fallen to less than half its normal value.2. The behaviour of the thrombin time is the manifestation of an important difference between the coagulation defect in hepatitis and that on administration of Sintrom.